Badger vaccination in England: Progress, operational effectiveness and participant motivations. Issue 3 (26th May 2020) - Benton, Clare H.; Phoenix, Jess; Smith, Freya A. P.; Robertson, Andrew; McDonald, Robbie A.; Wilson, Gavin; Delahay, Richard J.
Abstract: In 2010 a vaccine was licensed for use in badgers in the United Kingdom to reduce the severity of Mycobacterium bovis infection, and hence the risks of onward transmission to cattle. National legislation was enacted to allow its deployment by lay persons, but the efficiency and feasibility of badger vaccination has been the subject of ongoing debate. We conducted quantitative analysis on badger vaccination records and undertook interviews and participant observation on a sample of vaccination project participants in order to investigate (a) progress in the deployment of badger vaccination in England, (b) the trapping efficiency and coverage achieved by non‐government groups, (c) motivations of participants involved in vaccination projects and (d) barriers to wider implementation. Between 2010 and 2015 the number and distribution of vaccine deployment projects increased substantially, spreading from two to 17 English counties. Estimates of badger trapping efficiency for non‐government groups did not differ from those achieved by highly experienced government operatives. Our estimate of vaccine coverage (i.e. the average proportion of the target badger population vaccinated during an operation) was 57% (range 48%–63%). Interviews and participant observation revealed a range of motivations among individuals involved in badger vaccination including disease control, demonstration of an alternative to badger culling and personal or professional development. Barriers to wider adoption of badger vaccination expressed by interviewees related primarily to a perceived lack of confidence among farmers and landowners in the effectiveness of badger vaccination for bTB control, but also to the limited availability of funding. Our study suggests that badger vaccination led by non‐governmental groups is practically feasible, and may achieve levels of coverage consistent with disease control benefits. Wider uptake of badger vaccination across England might potentially be achieved by addressing the knowledge gap of the effect of badger vaccination on cattle TB, working closely with farmers and vets to better communicate the evidence base (in order to increase confidence in badger vaccination as a viable disease management approach), and by increased financial support for new initiatives and the scaling up of existing projects. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.